Outcome of Endoscopic Ultrasound-Guided Sampling of Mediastinal Lymphadenopathy - Tae Young Park; Jeong Seop Moon (Gastroenterology Research and Practice)
Background and Objectives. Endoscopic ultrasound (EUS)- guided transesophageal fine needle biopsy has been used as a method for histologic evaluation of mediastinal lymph nodes (LNs). This study aimed to compare the outcomes of the EUS-guided sampling with mediastinal lymphadenopathy using a 19-gauge trucut needle and 22-gauge fine needle aspiration (FNA) needle. Methods. From May 2006 to January 2017, patients with mediastinal lymphadenopathy, who received an EUS-guided trucut biopsy or an FNA biopsy, were retrospectively reviewed. Demographic data, endosonographic characteristics of LNs including size, shape, border, echotexture, and echogenicity, diagnostic yield, and adverse events between the trucut needle group and aspiration needle group were compared. Results. A total of 69 patients (trucut group, n=33 vs. aspiration group, n=36) were identified. There were no significant differences in demographic data, indication for an EUS-guided biopsy, location of LNs, number of needle passes, and endosonographic features of LNs between the two groups. The sizes of LNs were larger in the trucut group than in the aspiration group (28.9±14.0 mm vs. 21.1±8.8 mm, P=0.007). However, there was no significant difference in the ratio of LNs that were ≥10 mm in both groups. The overall accuracy of the EUS-guided biopsy for the diagnosis of malignant lesions was 79.7% (55/69). There were no significant differences in the histological diagnostic yield of malignant LNs between the two groups. There were no significant procedure-related adverse events in both groups. Conclusion. The EUS-guided biopsy can be a useful method for histologic evaluation of mediastinal nodal lesions.